Falls from height a guide to rescue planning - McCurley, Loui, 1965- (Wiley, 2013)
"Occupational fall protection has grown substantially as a safety practice over the past two decades. This book guides the reader in creating a comprehensive plan for post-fall rescue and retrieval in the workplace. Chapters lay out, step by step, a valuable roadmap to follow in developing specific plans for effecting prompt rescue at work locations. This essential book for safety managers and planners aids the employer in making informed decisions in advance about the who, what, when, and how of emergency rescue in the critical first moments following an accidental fall"--